2013
DOI: 10.1063/1.4789454
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen transport diagnostics by atomic and molecular emission line profiles simultaneously measured for large helical device

Abstract: We observe the Balmer-a, -b, and -c lines of hydrogen atoms and Q branches of the Fulcher-a band of hydrogen molecules simultaneously with their polarization resolved for large helical device. From the fit including the line splits and the polarization dependences by the Zeeman effect, the emission locations, intensities, and the temperatures of the atoms and molecules are determined. The emission locations of the hydrogen atoms are determined outside but close to the last closed flux surface (LCFS). The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 33 publications
3
22
0
Order By: Relevance
“…Furthermore, the hot neutral temperature had anisotropy (T ⊥ > T || ). Even though the preceding studies already observed the hot neutral flow [15][16][17], the observation of the temperature anisotropy in hot neutrals is the very first. The dependencies of hot neutral temperature and anisotropy were consistent with ions.…”
Section: Summary and Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Furthermore, the hot neutral temperature had anisotropy (T ⊥ > T || ). Even though the preceding studies already observed the hot neutral flow [15][16][17], the observation of the temperature anisotropy in hot neutrals is the very first. The dependencies of hot neutral temperature and anisotropy were consistent with ions.…”
Section: Summary and Discussionmentioning
confidence: 98%
“…The dependencies of hot neutral temperature and anisotropy were consistent with ions. Since hot neutrals emitting a broad component are mainly produced by charge exchange between neutrals and protons [17], the flow and the anisotropy were inherited from protons. Therefore, our observation is the evidence of proton temperature anisotropy in RT-1.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the purpose of further improving this technique, we recently demonstrated a method to observe several emission spectra of hydrogen atoms and molecules simultaneously with developing a multi-wavelength highresolution (MH) spectrometer [16,17]. From the observed Zeeman splits of the atomic and molecular lines, we have shown the difference of the atomic and molecular emission locations in the LHD [18]. In this paper, we describe the multiple LOSs measurement of the atomic and molecular emissions for the investigation of the location and intensity distributions in the LHD.…”
Section: Introductionmentioning
confidence: 99%